Doktrinarna konstrukcija Slovenije do leta 1914 - Lukšič, Igor (Teorija in praksa, 2015)
In Slovenian territory ideological configuration was developing and obtained its crucial points in the context of establishing modern politics, which corresponds with the emergence of capitalism. On the level of ideology, capitalism reflected itself mostly through the Reformation. Modern ideologies developed in the Enlightenment and obtained their clear form in the French Revolution. By the end of the 19th century, three main ideologies prevailed and were organised in three main parties: the conservative Catholic Slovenian People's Party, the socialist social democracy and the liberal (national) party. Yet the strongest impact on the Slovenian political arena came from the struggle for national autonomy and gaining political support to create the administrative framework for unifying the entire Slovenian nation. Compared to other European nations where the citizenry represented the major force in creating national independence, the Slovenian citizenry was too weak to put on the agenda for that. Because no political force among Slovenians was strong enough, political ideologies also became underdeveloped and were more subdivisions of corporatism: conservatism, liberalism, socialism and nationalism. Corporate nationalism was a common denominator of all three.
Keywords: Conservativism; Corporate state; Konservativizem; Korporativizem; Liberalism; Liberalizem; Nacionalizem; Nationalism; political party; politična zgodovina; politične doktrine; politične stranke; Slovenia; Slovenija; Socialism; Socializem